2012
DOI: 10.1016/j.jvs.2011.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the upper and lower landing site after endovascular aortic aneurysm repair

Abstract: Our results show a trend toward dilatation of the aortic neck and iliac arteries, with no correlation between the two levels, even in patients with a regression of the aneurysm sac during follow-up. Although this study found no correlation with the occurrence of endoleaks, our results suggest the need for a longer follow-up, especially on the landing sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…Although they could not find a correlation with clinical events, the authors sent a word of caution. 2 Previously, Falkensammer et al had shown that dilatation was more pronounced in patients with previously existing iliac dilatation, 9 and both Hobo et al and Albertini et al reported a higher risk of complications in patients requiring bellbottom (!24 mm) iliac limbs, a finding corroborated by the present study. 6,10 Similarly, Schanzer et al reported a greater chance of sac enlargement in patients with larger (20 mm or greater) iliac diameter endografts.…”
Section: Discussionmentioning
confidence: 98%
“…Although they could not find a correlation with clinical events, the authors sent a word of caution. 2 Previously, Falkensammer et al had shown that dilatation was more pronounced in patients with previously existing iliac dilatation, 9 and both Hobo et al and Albertini et al reported a higher risk of complications in patients requiring bellbottom (!24 mm) iliac limbs, a finding corroborated by the present study. 6,10 Similarly, Schanzer et al reported a greater chance of sac enlargement in patients with larger (20 mm or greater) iliac diameter endografts.…”
Section: Discussionmentioning
confidence: 98%
“…All these studies suggest that arterial areas in contact with the endograft tend to remodel toward expansion in a non-negligible number of patients and that aneurysmal disease progresses, even after graft exclusion. 13 Consequently, one can assume that the natural evolution of an already enlarged CIA trends towards an even more progressive growth of diameter.…”
Section: Discussionmentioning
confidence: 99%
“…24 This aneurysmal degeneration of the distal sealing zone after EVAR with the consequent type Ib endoleak as well as the development of a para-anastomotic aneurysm after open aortoiliac reconstruction is another frequent phenomenon that can complicate the follow-up of AAA patients and increase the risk of post-treatment rupture. 25 Several reports on successful treatment of these complications with commercially available IBDs are published. 15,26,27 We have identified two patients in our cohort who had developed a pseudoaneurysm after a bilateral open aortoiliac reconstruction and two other patients with type Ib endoleak after EVAR.…”
Section: Discussionmentioning
confidence: 99%